2020
DOI: 10.3390/ijerph17062109
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Transmission of Staphylococcus Aureus in the Intensive Care Unit

Abstract: Staphylococcus aureus is an important bacterial pathogen. This study utilized known staphylococcal epidemiology to track S. aureus between patients, surfaces, staff hands and air in a ten-bed intensive care unit (ICU). Methods: Patients, air and surfaces were screened for total colony counts and S. aureus using dipslides, settle plates and an MAS-100 slit-sampler once a month for 10 months. Data were modelled against proposed standards for air and surfaces, and ICU-acquired staphylococcal infection. Whole-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
1
7
0
3
Order By: Relevance
“…This failure rate of air cleaning is higher than that found by Adams and Dancer [ 17 ], who evaluated the contamination of a hospital environment that used mechanically ventilated air, with 10 air changes per hour, and constant temperature, and humidity. In their study, half of the exposed plates produced counts of >1 CFU/plate and the hygiene failure rate was 50%.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…This failure rate of air cleaning is higher than that found by Adams and Dancer [ 17 ], who evaluated the contamination of a hospital environment that used mechanically ventilated air, with 10 air changes per hour, and constant temperature, and humidity. In their study, half of the exposed plates produced counts of >1 CFU/plate and the hygiene failure rate was 50%.…”
Section: Discussionmentioning
confidence: 66%
“…multidrug resistance (MDR) is responsible for 2% to 5% of HAIs in the NICU and causes significant neonatal morbidity and mortality (20–35%) [ 11 , 15 , 16 ]. These microorganisms can survive for long periods on inanimate surfaces and in the air [ 3 , 15 , 17 ]. Studies have shown that the persistence of MDR isolates in the environment can vary from 7 days to 5 years, depending on the type of surface, humidity, and temperature, persisting longer on dry surfaces [ 3 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital infections are caused by factors such as environmental contamination, frequent handling of contaminated material, and the ability of microorganisms to survive for prolonged periods on different types of surfaces [ 1 , 92 ]. Within the hospital environment, sodium hypochlorite is the most widely used disinfectant because it has broad-spectrum antimicrobial activity, considering Gram-positive and Gram-negative bacteria and fungi [ 83 ] as well as demonstrated virucidal activity [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that a high bacterial load is an indicator of the presence of potentially pathogenic microorganisms. In a study by Adams et al [ 27 ] investigating the occurrence of Staphylococcus aureus in a human intensive care unit, most Staphylococcus aureus were detected on heavily contaminated hand-touch sites. This study has shown that dental procedures, using handpieces, contaminate the equipment and the surrounding environment, with a potentially increased risk of transmission of pathogens between patients, staff, and facilities.…”
Section: Discussionmentioning
confidence: 99%